1999
DOI: 10.1080/08035259950168469
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions to unlicensed and off-label drugs on paediatric wards: a prospective study

Abstract: To determine the incidence of adverse drug reactions (ADRs) to unlicensed and off-label drugs used in paediatric inpatients, we carried out prospective surveillance on five different paediatric wards in a regional children's hospital for 13 wk. Comparison of the use of each drug with its summary of product characteristics was made to determine whether the drug was used in an unlicensed or off-label manner. The presence of an ADR was determined using previously defined criteria. In total, 4455 courses of drugs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
130
3
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(145 citation statements)
references
References 17 publications
8
130
3
4
Order By: Relevance
“…We found an overall ADR incidence of 13.1% (95% CI, 9.8–16.3) which is slightly above the findings published previously [5], [6], [8], [12]. However, it is still lower than the overall incidence observed in our large international multi-centre study [15].…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…We found an overall ADR incidence of 13.1% (95% CI, 9.8–16.3) which is slightly above the findings published previously [5], [6], [8], [12]. However, it is still lower than the overall incidence observed in our large international multi-centre study [15].…”
Section: Discussioncontrasting
confidence: 53%
“…It has been shown that the incidence of ADRs in hospitalized children is about 10% [5], [6], [8],[12]. A large systematic review by Smyth et al indicated that the incidence rate for ADRs causing hospital admission is 2.9% [11].…”
Section: Introductionmentioning
confidence: 99%
“…In pediatrics, drugs are often prescribed using dosage and indications approved for adults, resulting in increased risk of serious adverse events (including drug therapeutic failure). [1234] Moreover, physicians when administering drugs to children are frequently forced to deviate from the established labelling indications, by manipulating drug formulation to obtain a pediatric dose or by changing the indicated route of administration. [5] Off-label prescribing could be related to several problems such as safety for the patient, costs for the society, and legal risk for the physician; therefore, this practise should be used only when the benefit outweighs the risk.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that off-label drug use in pediatrics is associated with significantly increased risk for developing adverse drug reactions. 27,28 …”
Section: Opportunities and Challengesmentioning
confidence: 99%